Manajemen Supervisi Pendidikan Untuk Meningkatkan Kelancaran Pembelajaran dan Minat Baca Bagi Peserta didik - Ibniyatus Shalihah (Lembaga Einstein College (LEC), 2024)
Abstrak This article discusses management which management is used to improve the smoothness of learning and reading interest for students. Educational supervision has an important role as supervision in carrying out activities that can be done in the form of a learning process and reading interest. This study uses a qualitative approach using library research which is used as an instrument in data collection. Therefore, the results of the study can show that educational supervision includes a mentoring process carried out from superiors to subordinates in order to improve and also improve the smoothness of learning and reading interest for students so that they can create quality educational institutions